Poor management of hypertension is an important precipitating factor for the development of acute aortic dissection. Issue 6 (20th May 2019) - Dong, Ning; Piao, Hulin; Li, Bo; Xu, Jian; Wei, Shibo; Liu, Kexiang
Abstract: Hypertension is considered a key risk factor for acute aortic dissection (AAD). However, there is limited evidence demonstrating if hypertension management affects AAD development. The objective of this study was to investigate the role of hypertension management in AAD development in a Chinese population. A total of 825 AAD patients and 3300 age‐ and sex‐matched controls were included. The authors analyzed data on demographics, chronic comorbidities, and hypertension management of all participants. Multiple logistic regression analysis was used to estimate the adjusted odds ratios (AOR) and 95% confidence intervals (95% CI) for the relationship between chronic comorbidities, as well as the management of hypertension and AAD risk. After adjusting for other related factors, multivariate logistic regression identified hypertension, chronic kidney disease, Marfan syndrome, history of cardiovascular surgery, and history of smoking as risk factors for AAD. Among the identified risk factors, hypertension was an important and controllable risk factor for AAD development. Thus, the authors further evaluated how hypertension management affects AAD development. A total of 848 controls and 585 AAD patients with hypertension were enrolled in this part of the study. Hypertensive patients with AAD had a longer history, higher stage, poorer medication compliance, and poor control rates of blood pressure, among which poor medication compliance (Irregular vs Regular P  < 0.001; Never treated vs Regular P  < 0.001) and uncontrolled hypertension ( P  < 0.001) significantly increased the risk of AAD development. In conclusion, uncontrolled hypertension and poor medication compliance are important precipitating and controllable factors for AAD development.